Adsorption of Copper and Zinc from Aqueous Solutions by Bentonite - TOMUL*, FATMA; TURGUT BASOGLU†, FUNDA (Asian Journal of Chemistry, 2009)
Bentonite has been used as an adsorbent for the removal of Cu2+ and Zn2+ ions from aqueous solutions via adsorption. The effect of the adsorbent amount, pH of suspension, solution concentration and temperature and the contact time on adsorption was investigated. The amount of Cu2+ and Zn2+ ions adsorbed increased with increasing adsorbent amount, pH and temperature and with decreasing concentration. The adsorption parameters were obtained using Reciprocal Langmuir, Langmuir, Linear Freundlich, Freundlich and Langmuir-Freundlich isotherm models by use of non linear regression analysis. The adsorption isotherm studies indicated that adsorption was consistent with the Reciprocal Langmuir isotherm model. Results of the thermodynamic studies indicated that the adsorption of both ions on bentonite was spontaneous and favourable and an endothermic nature of adsorption. A pseudosecond order equation described the adsorption process for either Cu2+ or Zn2+. The results of this study demonstrated that the bentonite is a potential adsorbent for the removal of Cu2+ and Zn2+ ions from aqueous solutions.